Effect of Diosgenin on the Circulating MicroRNA Profile of Ovariectomized Rats - Zhang, Zhiguo; Xiang, Lihua; Wang, Yuhan; Jiang, Yanhua; Cheng, Yin; Xiao, Gary Guishan; Ju, Dahong; Chen, Yanjing (Frontiers in Pharmacology, 2020)
The present study aimed to assess the changes in circulating microRNA (miRNA) expression profiles associated with the potential osteoprotective effect of diosgenin (DIO) in ovariectomized (OVX) rats. Wistar rats (female) were subjected to an sham operation (SHAM group) or ovariectomy. OVX rats were treated with DIO (DIO group) or vehicle (OVX group) for 12 weeks. Following treatment, the serum estradiol levels and the microarchitecture of tibias were assayed. Based on miRNA microarray and qRT-PCR analyses, differentially expressed (DE) circulating miRNAs were identified between the OVX and SHAM groups (comparison A) and between the DIO and OVX groups (comparison B). Furthermore, putative target genes of shared DE miRNAs with opposite expression trends in the two comparisons were predicted by Ingenuity Pathway Analysis (IPA). Finally, the expression levels of the putative target genes in serum and tibia were validated by qRT-PCR. The micro-CT results demonstrated that DIO had a substantial anti-osteopenic effect on the tibias of OVX rats. In total, we found 5 DE circulating miRNAs (4 upregulated and 1 downregulated) in comparison A and 21 DE circulating miRNAs (15 upregulated and 6 downregulated) in comparison B. However, only one DE circulating miRNA (rno-miR-20a-5p) had opposite expression trends between the two comparisons. Including rno-miR-20a-5p, 7 of the 10 selected DE circulating miRNAs between the two comparisons passed qRT-PCR validation. Specifically, based on qRT-PCR validation, DIO upregulated the expression of rno-miR-20a-5p and downregulated that of three target genes (Tnf, Creb1 and Tgfbr2) of the “osteoclast differentiation” pathway in the tibias of OVX rats. Our results suggested that DIO could change the circulating miRNA profile of OVX rats and inhibited the downregulation of miR-20a-5p in serum and tibia. DIO might exert an anti-osteoclastogenic effect on OVX rats by upregulating the expression of miR-20a-5p in circulation and bone tissue.